3D porous graphene films with large-area in-plane exterior skins - Tay, Roland Yingjie (2022)
Construction of macroscopic three-dimensional (3D) architectures of graphene is crucial to harness the advantageous properties of planar 2D graphene and to enable integration to many conventional and novel applications. Ideally, the 3D structure of graphene should be free of defects, covalently interconnected and can be produced at large-scale. Among various assembly techniques, fabrication using chemical vapor deposition (CVD) enables the production of high-quality graphene where selection of template is key that determines its consequent crystalline quality and structural morphology. Herein, we present a new method to synthesize high-quality porous graphene film by incorporating an in-situ reduction-oxidation cycling treatment to generate micrometer-sized pores on commercial Ni foil using an all-CVD process route. Owing to the unique morphological features of the modified Ni template, the graphene film exhibits a holey surface with large-area exterior skin coverage of >94% and many interconnected ligaments within its porous interior. This extraordinary configuration give rise to superior in-plane electrical conductivity despite its low density. In comparison to state-of-the-art materials for electromagnetic interference shielding, this porous graphene film is among the best performing materials with a specific shielding effectiveness of >550 dB cm3 g-1 and absolute effectiveness of >220,000 dB cm2 g-1.